2019
DOI: 10.1111/cea.13538
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil cytolysis on Immunoglobulin G is associated with microtubule formation and suppression of rho‐associated protein kinase signalling

Abstract: Esnault and Leet have participated equally to the work.Abbreviations: CD32, receptor for Fc fragment of IgG, low affinity II (FCGRII); DAPI, 4′,6-diamidino-2-phenylindole; DPI, diphenyleneiodonium; EDN, eosinophil-derived neurotoxin;HA-IgG, heat-aggregated immunoglobulin G; MAP4, microtubule-associated protein 4; MAPK, mitogen-activated protein kinase; MT, microtubule; NADPH, dihydronicotinamide-adenine dinucleotide phosphate; PFA, paraformaldehyde; PI3K, phosphatidylinositol 3'-kinase; ROCK, Rho-associated, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 67 publications
(99 reference statements)
5
23
0
Order By: Relevance
“…Eosinophil presence in the asthmatic airway is associated with increased disease severity and risk of exacerbations [ 1 , 2 ]. Airway eosinophils contribute to allergic inflammation in asthma by releasing a variety of soluble mediators and cell-free granule proteins through cytolysis and degranulation [ 3 , 4 , 5 ]. These factors contribute to the pro-inflammatory activation of other cell types, including bronchial fibroblasts, resulting in prolonged tissue injury that can lead to airway remodeling and subsequent irreversible airflow obstruction in some subjects [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eosinophil presence in the asthmatic airway is associated with increased disease severity and risk of exacerbations [ 1 , 2 ]. Airway eosinophils contribute to allergic inflammation in asthma by releasing a variety of soluble mediators and cell-free granule proteins through cytolysis and degranulation [ 3 , 4 , 5 ]. These factors contribute to the pro-inflammatory activation of other cell types, including bronchial fibroblasts, resulting in prolonged tissue injury that can lead to airway remodeling and subsequent irreversible airflow obstruction in some subjects [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we sought to begin to answer this question by utilizing an ex vivo model of human primary eosinophil cultures that both recapitulates the phenotype of asthmatic airway eosinophils and also enables inducible cytolysis and degranulation on heat-aggregated immunoglobulin G (IgG), mimicking eosinophil interactions with immunoglobulins found in vivo [ 5 , 6 , 17 ]. Using this model, we isolated the supernatants from cytolyzing and degranulating eosinophils, and, using a global transcriptomic approach, found that exposure of human lung fibroblasts to the complete milieu of eosinophil-derived soluble mediators results in the development of a pro-inflammatory gene expression profile [ 7 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have finally entered the much‐anticipated era of personalized medicine for asthma, and several articles evaluated biologics and the variation in individual response to these in people with asthma 25‐27 , 28‐36 , 37 , 38 Others evaluated more traditional treatments for asthma, such as corticosteroids or mechanisms that may underlie impaired airway function in asthma 39‐59 . New interventions studied in clinical trials included air cleaners, triple inhaler therapy, an oral prostaglandin D2 antagonist 60‐62 and other more preliminary data from various interventions, from cinnamon and bacterial peptides to allergen immunotherapy 63‐67 .…”
Section: Asthmamentioning
confidence: 99%
“…This study looked at IL-3-primed eosinophils seated on immunoglobulins like IgG. When eosinophils were exposed to IL-3, they degranulated early in the presence of IgG and the cytolysis of the IL-3-primed eosinophils was dependent on ROS production and involved eosinophil migration and adhesion [209].…”
Section: Eets and Inflammatory Diseasesmentioning
confidence: 99%